Caracterización de los desechos sólidos generados en el casco urbano de la parroquia Zumbahua, cantón Pujilí, provincia de Cotopaxi, período 2013 – 2014 - Laverde Albarracín, Emerson Javier (2014)
The present research work consisted on the characterization of the solid waste generated in the urban area of Zumbahua parish, Pujilí canton, Cotopaxi province, period 2013 - 2014, after a study carried out from the source (addresses) to final disposal (municipal dump), it became to clear that there was not an adequate treatment of solid waste, for that reason it creates a proposal to implement a management plan of solid waste, in order to achieve on integral risk of solid waste in the area....